Language mixing among Malay-English bilingual children: a case study in an informal art class / Farina Abdul Jabar - Abdul Jabar, Farina (2011)
There have been many studies conducted regarding the use of code-switching in language contact. However, case studies on the communicative intents of switchers and the ends to which these speakers seek in a particular setting are few and far between, especially with regards to childhood bilingualism in Malaysia. Therefore this research was conducted to explore the functions of code-switching among Malay-English bilingual children as described by Gumperz (1982), Halliday (1975), Kow (2003) and Malik (1994), via the discourse analysis of two Malay-English bilingual children and identifying the communicative strategies employed by these children in discourse. All the findings of this study which were obtained through qualitative means (discourse analysis) showed that children employed language mixing (with particularly interest in code-switching) to fulfill several communicative functions such as to facilitate expression, to communicate meaning when there is a lack of register, to emphasize a point, to imply semantic significance, in response to habitual experience and as repetition. However there are limitations to this research in that it could present generalized findings since the study will focus on a limited number of children in a specific setting. The implications of this study should provide educators with insight on their role in the development of bilingual curriculum materials and construction of bilingual instructional methodology implicit in second language learning.